Decision making Approach for Evaluation of Teaching Performance using Octagonal fuzzy number matrix - Santhi, S.; Selvakumari, K. (International Journal of Engineering and Technology, 2018)
Decision making method is useful in selecting the best alternatives among the selected alternatives. Under a fuzzy environment, the decision making enable the decision maker to choose their own opinion. The purpose of this paper is to propose a new approach for solving a attribute values of octagonal fuzzy number using decision making problems. We have to use the octagonal fuzzy number and octagonal fuzzy number matrix to select the overall performance of a teacher for the betterment of students, institution & society.Â Â